The theory of combinations for land plot exchange modelling in the course of land consolidation - Malashevskyi Мykola; Malashevska, Olena (Geodesy and Cartography, 2022)
The paper is aimed at the promotion of voluntary land consolidation through the improvement of land plots exchange. The issue of the existing land plots boundaries adjustment in the course of voluntary land consolidation has been singled out. Possibilities, advantages and risks of land plots exchange without changing the existing boundaries as a constituent of land consolidation measures have been substantiated. The improvement of approaches to land plots exchange modelling without the existing boundaries adjustment has been suggested. Demands to the formation of consolidated land tenures as the result of exchange have been singled out. Theory of combinations has been applied to specify land plots exchange options. Calculation formulas for the number of the optimal consolidated agricultural land tenure placement options have been suggested. The calculations can be applied in the optimization and heuristic approaches to land reallocation and at land consolidation performance evaluation. Suggested approaches facilitate the implementation of heuristic methods especially in non-standard conditions, allow to increase the number of developers, especially involving experts with little experience. The results can be used for land plots lease optimization.